The Influence of Disaster Safety Awareness on the Safety Competency of College Students - Won Hee Chung; Gie Ok Noh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With various social disasters such as fire and COVID-19 occurring recently along with natural disasters, the problem of young people's insensitivity to safety has emerged. It is important to understand what causes the lack of disaster safety awareness among college students, and to understand how this lack of disaster safety awareness affects safety competency. 2,236 college students' questionnaires on self-reported disaster safety awareness and competency were collected. Data were statistically analyzed with descriptive statistics, independent t-test, factor analysis and multiple regression analysis using the SPSS 25.0 program. Greater personal (basic) awareness (β = .53), social awareness (β = .44), and cultural awareness (β = .38) of disaster safety were associated with greater safety competency. Disaster safety awareness explained 61.7% of their safety competency. Efforts are required to promote individual and social competency against disasters by running programs to continuously raise disaster safety awareness among college students.